A Review of Article "Alms-giving" in Encyclopedia of the Quran - Seyed Abdolrahim Hosseini; Seyyed Mohammad Musavi Moqaddam; Omolbanin Soleymani Baghshah (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Leiden Encyclopedia of the Quran is the newest comprehensive research work in the West about the interpretive studies of the Quran accomplished from 2000 to 2006 by the Chief Editor, Jane Dammen McAuliffe, in the city of Leiden in the Netherland and published by Brill Publishers. The article Zakat (alms-giving) written by a researcher named Azim Nanji has been published in the first volume of the Leiden Encyclopedia of the Quran (pp. 64 -70). The most important issues and themes that have been criticized and reviewed in the view of the authors of the article include the essence and the constitutive elements of sadaqah (charity), the ideal donation and its aspects in the view of the Holy Quran, the relationship between piety and donation, the synonymous concepts of sadaqah, the status and the aspects of sadaqah, the semantics and the conditions for the payment of zakat, and the process of formation of the institution of sadaqah and its distribution. The above-mentioned issues, while focusing on the original and valid sources in the two perspectives of unfinished, biased perceptions and presenting a different and undocumented interpretation of the teachings of the Islamic traditions, interpretation, and the clear texts of the Quran, have been critically reviewed with a look on their different aspects